Pengaruh Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Indomarco Prismatama Tangerang 1 - Ratnawati, Whina (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to determine the effect of work discipline on employee performance. To determine the effect of the work environment on employee performance. To determine the effect of work discipline and work environment on employee performance at PT. Indomarco Prismatama Tangerang 1. This research method is quantitative and the nature of this research is associative. The population in this study were all baristas pointcoffee Tangerang 1 PT. Indomarco Prismatama 87 people. By using saturated sampling, a sample of 87 respondents was obtained. The results of the study showed that work discipline had a positive and significant effect on employee performance, this is evidenced by the t-count value of 14.235> t-table 1.989 and the sig value of 0.000 <0.05, so the decision was taken H01 was rejected and Ha1 was accepted. The work environment does not have a positive and significant effect on employee performance, this is evidenced by the t-count value of -0.448 <t-table 1.989 and the sig value of 0.655> 0.05 so H02 was rejected and Ha2 was accepted. Work discipline and work environment have a positive and significant effect on employee performance, this is evidenced by the Fcount value of 100.231> Ftable 3.10 and the sig value of 0.000 <0.05 so that H03 is rejected and Ha3 is accepted. The Adjusted R Square determination coefficient of 0.698 states that the work discipline (X1) and work environment (X2) variables have a contribution of 69.8% to performance (Y) and the remaining 30.2% is influenced by other factors.